The relation between race-related implicit associations and scalp-recorded neural activity evoked by faces from different races. - He, Yi; Johnson, Marcia K; Dovidio, John F; McCarthy, Gregory (Social neuroscience, 2009)
The neural correlates of the perception of faces from different races were investigated. White participants performed a gender identification task in which Asian, Black, and White faces were presented while event-related potentials (ERPs) were recorded. Participants also completed an implicit association task for Black (IAT-Black) and Asian (IAT-Asian) faces. ERPs evoked by Black and White faces differed, with Black faces evoking a larger positive ERP that peaked at 168 ms over the frontal scalp, and White faces evoking a larger negative ERP that peaked at 244 ms. These Black/White ERP differences significantly correlated with participants' scores on the IAT-Black. ERPs also differentiated White from Asian faces and a significant correlation was obtained between the White-Asian ERP difference waves at approximately 500 ms and the IAT-Asian. A positive ERP at 116 ms over occipital scalp differentiated all three races, but was not correlated with either IAT. In addition, a late positive component (around 592 ms) was greater for the same race compared to either other race faces, suggesting potentially more extended or deeper processing of the same race faces. Taken together, the ERP/IAT correlations observed for both other races indicate the influence of a race-sensitive evaluative process that may include early more automatic and/or implicit processes and relatively later more controlled processes.
Keywords: Brain; Brain Mapping; Continental Population Groups; Electroencephalography; Evoked Potentials, Visual; Face; Facial Expression; Female; Gender Identity; Humans; Male; Neuropsychological Tests; Pattern Recognition, Visual; Photic Stimulation; Reaction Time; Social Identification; Statistics as Topic; Young Adult